Checkpoint Inhibitors, CAR T Cells, and the Hemostatic System: What Do We Know So Far? - Rolling, Christina C.; Lewirt, Samuel; Beitzen-Heineke, Antonia; Beckmann, Lennart; Bokemeyer, Carsten; Alsdorf, Winfried; Voigtlaender, Minna; Langer, Florian (Hämostaseologie, 2025)
Immune checkpoint inhibitors (ICIs) and chimeric antigen receptor (CAR) T cells are novel therapeutic strategies that enhance anticancer immunity by activating or engineering cancer-targeting T cells. The resulting hyperinflammation carries several side effects, ranging from autoimmune-like symptoms to cytokine release syndrome (CRS), with potentially severe consequences. Recent findings indicate that ICIs increase the risk of venous and arterial thromboembolic adverse events. Patients with prior VTE might be at higher risk of developing new events under ICI while other risk factors vary across studies. So far, data on CAR T-linked coagulopathies are limited. Hypofibrinogenemia in the presence of CRS is the most commonly observed dysregulation of hemostatic parameters. A rare but particularly severe adverse event is the development of disseminated intravascular coagulation activation, which can occur in the setting of CRS and may be linked to immune effector cell-associated hemophagocytic lymphohistiocytosis. While the increasing number of studies on thromboembolic complications and coagulation alterations under ICIs and CAR T therapies are concerning, these results might be influenced by the retrospective study design and the heterogeneous patient populations. Importantly, numerous promising new T cell-based immunotherapies are currently under investigation for various cancers and are expected to become very prominent therapy options in the near future. Therefore, coagulopathies and thrombosis under T cell-directed immuno- and anti-cancer therapies is important. Our review provides an overview of the current understanding of ICI- and CAR T-associated thromboembolism. We discuss pathogenic mechanisms of inflammation-associated coagulation activation and explore potential biomarkers for VTE.
Keywords: immune checkpoint inhibitors; CAR T cells; hypercoagulability; thromboinflammation; cancer